PENGARUH MEDIA BOOKLET SEBAGAI INOVASI EDUKASI PERTOLONGAN PERTAMA PADA KECELAKAAN (P3K) UNTUK MENINGKATKAN PENGETAHUAN REMAJA DI MTS “NH” LUBUK BATU JAYA TAHUN 2025 - ainil fitri; Sukarni; Dyas Nisa Ayu (Jurnal Keperawatan Abdurrab, 2026)
Adolescent knowledge of first aid in accidents (P3K) plays an essential role in reducing the risk of further injury during incidents that occur in the school environment. However, limited access to information and low exposure to first-aid materials remain obstacles for this age group. This study aims to analyze the influence of booklet media as a P3K educational innovation in increasing adolescent knowledge at MTs “NH” Luluk Batu Jaya in 2025. A pre-experimental one-group pretest–posttest design was used, involving 54 students selected through accidental sampling. The intervention consisted of distributing a first-aid booklet accompanied by a guided educational session. Knowledge was measured using a standardized questionnaire administered before and after the intervention. The findings show a significant increase in knowledge scores after the booklet was provided. Prior to the educational intervention (pretest), 30 respondents (55.6%) had good knowledge, 23 respondents (42.6%) had moderate knowledge, and 1 respondent (1.8%) had poor knowledge. After the intervention, knowledge improved considerably, with 52 respondents (96.3%) demonstrating good knowledge, 2 respondents (3.7%) showing moderate knowledge, and none in the poor category. These results indicate that the booklet effectively enhanced adolescents’ understanding of basic first-aid procedures. The study confirms that booklets serve as an easy-to-implement, economical, and relevant educational medium to strengthen students’ preparedness for emergency situations in schools. The researchers recommend incorporating booklet-based education into continuous school health promotion programs as one of the key educational strategies.